Increasing The Competitive Advantage of PT. XYZ Through Product Differentiation For HVAC Chiller (HRS) Systems - Amnas Ridho Pane; Oviyan Patra; Evan Nugraha; Hendy Suryana (Eduvest - Journal of Universal Studies, 2026)
This document discusses the product differentiation strategy implemented by PT. XYZ to increase competitive advantage in the HVAC industry, especially chiller systems with Heat Recovery System (HRS). In the context of fierce competition, companies need to understand customer needs and create products that offer unique added value. This study uses quantitative methods to analyze important variables in attracting and retaining customers. The results show that focusing on product differentiation and service improvement can increase customer loyalty and, ultimately, sales volume. This research is expected to make a theoretical and practical contribution to the development of effective marketing strategies in the refrigeration industry.